Loss of central auditory processing in a mouse model of Canavan disease. - Georg von Jonquieres (Public Library of Science (PLoS), 2014)
Canavan Disease (CD) is a leukodystrophy caused by homozygous null mutations in the gene encoding aspartoacylase (ASPA). ASPA-deficiency is characterized by severe psychomotor retardation, and excessive levels of the ASPA substrate N-acetylaspartate (NAA). ASPA is an oligodendrocyte marker and it is believed that CD has a central etiology. However, ASPA is also expressed by Schwann cells and ASPA-deficiency in the periphery might therefore contribute to the complex CD pathology. In this study, we assessed peripheral and central auditory function in the AspalacZ/lacZ rodent model of CD using auditory brainstem response (ABR). Increased ABR thresholds and the virtual loss of waveform peaks 4 and 5 from AspalacZ/lacZ mice, indicated altered central auditory processing in mutant mice compared with Aspawt/wt controls and altered central auditory processing. Analysis of ABR latencies recorded from AspalacZ/lacZ mice revealed that the speed of nerve conduction was unchanged in the peripheral part of the auditory pathway, and impaired in the CNS. Histological analyses confirmed that ASPA was expressed in oligodendrocytes and Schwann cells of the auditory system. In keeping with our physiological results, the cellular organization of the cochlea, including the organ of Corti, was preserved and the spiral ganglion nerve fibres were normal in ASPA-deficient mice. In contrast, we detected substantial hypomyelination in the central auditory system of AspalacZ/lacZ mice. In summary, our data suggest that the lack of ASPA in the CNS is responsible for the observed hearing deficits, while ASPA-deficiency in the cochlear nerve fibres is tolerated both morphologically and functionally.